2006
DOI: 10.1128/iai.74.1.257-264.2006
|View full text |Cite
|
Sign up to set email alerts
|

Target Antigen, Age, and Duration of Antigen Exposure Independently Regulate Immunoglobulin G Subclass Switching in Malaria

Abstract: The isotype/subclass of immunoglobulin determines antibody function, but rather little is known about factors that direct class switching in vivo. To evaluate factors that might influence the maturation of the antibody response during infection, we conducted a seroepidemiological study of the immunoglobulin G (IgG) subclass response to four merozoite-associated antigens of Plasmodium falciparum in a mountainous region of northeastern Tanzania, where malaria endemicity declines with increasing altitudes. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
103
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 52 publications
29
103
2
1
Order By: Relevance
“…In early stages, it IgG subclass in membranous glomerulonephritis is possible that there is an IgG1-dominant anti-PLA2R response, which, with disease progression, will turn into an IgG4-dominant antibody response. Such IgG subclass switch has been reported in a variety of diseases, such as in malaria, 20 leprosy and tuberculosis, 21 and paracoccidioidomycosis. 22 A Recent study by Segawa et al 23 from Japan, describes the IgG subclass distribution in 16 pediatric patients with 'idiopathic' membranous glomerulonephritis.…”
Section: Discussionmentioning
confidence: 76%
“…In early stages, it IgG subclass in membranous glomerulonephritis is possible that there is an IgG1-dominant anti-PLA2R response, which, with disease progression, will turn into an IgG4-dominant antibody response. Such IgG subclass switch has been reported in a variety of diseases, such as in malaria, 20 leprosy and tuberculosis, 21 and paracoccidioidomycosis. 22 A Recent study by Segawa et al 23 from Japan, describes the IgG subclass distribution in 16 pediatric patients with 'idiopathic' membranous glomerulonephritis.…”
Section: Discussionmentioning
confidence: 76%
“…However, if natural recovery from infection (e.g., from asymptomatic to subpatent) is solely determined by age (via physiological processes, provided there is exposure on which infection is conditional), we obtain patterns closer to those observed ( Figure 3). This suggests that parasite immunity in non-naïve individuals may be controlled by physiological development rather than by the amount of natural exposure (provided there is exposure) [7][8][9]14,15,30].…”
Section: Improved Model For the Impact Of Immunity On Recovery From Amentioning
confidence: 99%
“…It has been suggested that IgG3 is more efficient at mediating these processes (7). For reasons that are not well understood, different merozoite antigens induce different relative levels of IgG1 and IgG3 (14,29,31,37,40,46,48). It is unclear whether individuals have a bias toward producing a specific subclass regardless of the antigen or if instead the IgG subclass response is generated independently for each antigen and how this relates to protective immunity.…”
mentioning
confidence: 99%
“…It is unclear whether individuals have a bias toward producing a specific subclass regardless of the antigen or if instead the IgG subclass response is generated independently for each antigen and how this relates to protective immunity. While factors determining subclass responses to antigens are not clearly defined, antigen properties, host age, cumulative exposure, and genetic determinants have been linked with the nature of subclass responses (2,4,17,33,34,41,42,47,48). Some studies have suggested that increasing age (and therefore malaria exposure) leads to an increasing polarization of IgG subclass responses to merozoite antigens (41,48).…”
mentioning
confidence: 99%
See 1 more Smart Citation